2005
DOI: 10.1002/cncr.21366
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of vascular endothelial growth factor‐C and vascular endothelial growth factor receptor 3 in patients with T1 lung adenocarcinoma

Abstract: The weight of characters is a crucial step in different population analyses. We propose a new formula to facilitate this while establishing a scale that follows the criteria of the probability of change in each character. This method is described for drawing of median‐joining networks, yet it could also be used for other methods in which the weight of the characters is required. Am J Phys Anthropol, 2010. © 2010 Wiley‐Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
25
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 47 publications
6
25
1
1
Order By: Relevance
“…Similar to our findings, VEGFR-2 has previously been localized to vessels, supporting BCs (16,17); however, there is only one report of upregulation on vessels (16) and the majority of other studies claim a breast tumor cell localization (22)(23)(24). Similar VEGFR-3 vascular expression data have been reported for BCs (27)(28)(29)(30) and NSCLCs (31); however, others report localization of VEGFR-3 to malignant breast (23,35) or lung cells (19,25,32,33,36,37). VEGFR-2 was originally shown to be restricted to vessels associated with CRCs (15).…”
Section: Relative Vascular Localization Of Vegfr-2 and Vegfr-3 In Prisupporting
confidence: 89%
See 2 more Smart Citations
“…Similar to our findings, VEGFR-2 has previously been localized to vessels, supporting BCs (16,17); however, there is only one report of upregulation on vessels (16) and the majority of other studies claim a breast tumor cell localization (22)(23)(24). Similar VEGFR-3 vascular expression data have been reported for BCs (27)(28)(29)(30) and NSCLCs (31); however, others report localization of VEGFR-3 to malignant breast (23,35) or lung cells (19,25,32,33,36,37). VEGFR-2 was originally shown to be restricted to vessels associated with CRCs (15).…”
Section: Relative Vascular Localization Of Vegfr-2 and Vegfr-3 In Prisupporting
confidence: 89%
“…one or the other receptor to tumor vessels (15,16,24,(26)(27)(28)(29)(30)(31), the majority report expression in malignant cells (18)(19)(20)(21)(22)(23)(24)(25)(32)(33)(34)(35)(36)(37). Antibodies from a single source have been used to produce the majority of data, suggesting that tumor cells express VEGFR-2.…”
Section: Relative Vascular Localization Of Vegfr-2 and Vegfr-3 In Primentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, as with other tumors, some studies did not report an association between VEGF-A expression and survival. [26][27][28][29][30] Another factor from the VEGF family that has been associated with poorer survival in patients with lung cancer is VEGF-C. [31][32][33][34] The analysis of VEGF family receptors has not provided conclusive evidence of their effects on the survival of Original Article cancer patients, except for VEGFR3/Flt-4, the expression of which has been associated with poorer survival in patients with lung cancer 32,34,35 and with other tumors. [36][37][38] However, although some studies of VEGFR1/Flt-1 and VEGFR2/Flk-1 demonstrated a relation between the expression of these 2 receptors and poorer survival, 16 others did not 14,39,40 ; and in the study by Zhukova et al, 41 VEGFR1 expression was associated to better survival.…”
mentioning
confidence: 99%
“…It correlates with shorter progression free survival (PFS), overall survival (OS) and lymph node metastasis in melanoma [12], and is a poor prognostic factor in nonsmall-cell lung cancer and adenocarcinoma of the lung [13,14]. High levels of VEGF-C expression in gastric cancer tissue imply worse overall prognosis than low VEGF-C levels [15].…”
Section: Introductionmentioning
confidence: 99%